Paisagens do Rio Grande do Norte: uma introdução às diversidades regionais e marcas das ações geográficas no espaço potiguar - Rodrigo de Freitas Amorim; Raimundo Nonato Junior; Juliana Felipe Farias Poster (Confins)
This article presents introductory reflections on the category of geographical landscape, considered in the context of the state of Rio Grande do Norte territory. It aims to propose new forms of reading and analysis of landscapes of the State. Classification of landscape forms are analyzed on the basis of the interaction between human and physical criteria in order to conceive a cross-sectional analysis methodology. The landscape units defined point to a dialogical relationship between the categories of landscape and the region, as well as to various forms of manifestation of these in geographical space. The diversity of elements on the morphology of the state is used to question the erroneous homogenizing vision of the landscape of the Brazilian Northeast. The data shows a landscape design that serves as an stimulus to think the hybrid condition of geographical epistemology in contemporary times, as well as their new forms of spatial configuration.